Magnetic properties of NiCuZn ferrites synthesized by oxalate precursor method - Ghodake, S. A.; Ghodake, U. R.; Sawant, S. R.; Suryavanshi, S. S.; Bakare, P. P. (Journal of Magnetism and Magnetic Materials, 2006)
Ni-Cu-Zn ferrites have been synthesized by employing co-precipitation technique using oxalate precursors. X-ray diffractograms did not show impurity phases, indicating single-phase formation of the ferrites. The diffractograms of oxalate complex decomposed at 650 degrees C show that ferritization is complete up to 650 degrees C. Lattice parameter a (angstrom) was found to decrease with the addition of Ni2+ which is attributed to ionic sizes of Ni2+ (0.69 angstrom), which replaces Cu2+ (0.72 angstrom). From the thermogravimetric studies it is observed that the experimentally observed total mass loss (%), agrees with theoretically calculated mass loss (%) indicating maintenance of requisite stoichiometry. Initial permeability (mu(i)) shows increase when Ni2+ is added up to x = 0.15 while for (x > 0. 15), it decreases. The increase in initial permeability (mu(i)) is attributed to monotonic increase in Ms, and K-1 on addition of Ni2+. However, the microstructure and density (porosity) also influence mu(i) variations. The decrease in pi is attributable to increase of K-1. The composition with density 91.14% exhibits large mu(i) which also tends to increase with temperature up to 60 degrees C. Thus its usable range extends up to 60 degrees C. This samples has T-c near to 160 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: initial permeability; magneticproperties; Magnetization; NiCuZn ferrites; XRD

Complex permeability studies of Ni-Co-Zn ferrites synthesized by an oxalate precursor method - Ghodake, J. S.; Kambale, R. C.; Kulkarni, S. D.; Sawant, S. R.; Suryavanshi, S. S. (Smart Materials & Structures, 2009)
Nanocrystalline Co-substituted Ni-Zn ferrites have been synthesized by employing a co-precipitation technique using oxalate precursors. The co-precipitated oxalates were decomposed in air at 650 degrees C for 1 h and the powder was sintered at 1000 degrees C. The phase formation of the sintered ferrite was confirmed by x-ray diffraction studies. The lattice parameter a (angstrom) increases with the addition of Co(2+) which is attributed to the large ionic size of Co(2+) (0.78 angstrom), which replaces Ni(2+) (0.74 angstrom). The crystallite size has been estimated by the Debye-Scherrer formula using the full width at half-maximum (FWHM) of the line broadening of the (311) reflection and it is found to be in the range of 25-28 nm. Also, with increasing cobalt content the magnetocrystalline anisotropy constant (K(1)) and magnetostriction constant (lambda(s)) increase, and the grain size decreases, hence the value of initial permeability mu(i) decreases. The saturation magnetization M(s) and magnetic moment (n(B)) do not show any significant variation for all compositions varying with the cobalt content.